The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2022
DOI: 10.18203/2394-6040.ijcmph20222003
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge and menstrual hygiene practices among adolescent secondary school girls in Ebonyi State, Nigeria

Abstract: Background: Menstrual hygiene is an aspect of sexuality education that people do not want to discuss publicly. Because of this most adolescent girl are bereaved of knowledge about menstrual hygiene practices. Therefore, the present study attempted to ascertain the knowledge and menstrual hygiene practices among adolescent secondary school girls in Ebonyi state, Nigeria.Methods: This was an institutional based cross-sectional study conducted from 11th July to 9th September 2021 among adolescent secondary school… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 21 publications
0
3
0
Order By: Relevance
“…Obande-Ogbuinya et al, 2022 [23] Secondary school girls in Ikwo local government area, Ebonyi State, Nigeria…”
Section: Most Community Settings Do Not Havementioning
confidence: 99%
See 2 more Smart Citations
“…Obande-Ogbuinya et al, 2022 [23] Secondary school girls in Ikwo local government area, Ebonyi State, Nigeria…”
Section: Most Community Settings Do Not Havementioning
confidence: 99%
“…Other authors also discovered the invaluable role played by school teachers to further educate girls about the basics of menstrual health [21]. It was revealed that 264 respondents were aware that genital tracts should be washed and had good knowledge of menstrual hygiene [23]. Some 59.7% of respondents did not know the causes of menses, channels through which menses flow, and intervals between menses.…”
Section: Knowledge Of Menstruation and Menstrual Hygiene Including So...mentioning
confidence: 99%
See 1 more Smart Citation